A fatty acid, flavonoids, and steroids from Zingiber penisulare. I. Theilade (zingiberaceae) - To Chinh, Truong Thi; Giang, Phan Minh; Son, Phan Tong (Vietnam Journal of Chemistry, 2014)
The first chemical study of Zingiber penisulare I. Theilade (Zingiberaceae) resulted in the isolation of a fatty acid, eicosanoic acid (1), three kaempferol derivatives, 5-hydroxy-3,4',7-trimethoxyflavone  (2), 4',5-dihydroxy-7-methoxyflavonol (5), and 4',5-dihydroxy-3,7-dimethoxyflavone (6), b-sitosterol (3), and 6b-hydroxystigmast-4-ene-3-one (4). Their chemical structures were determined by spectroscopic analyses. Keywords: Zingiber penisulare; Zingiberaceae; kaempferol; flavonol; stigmastane